Digital television in Brazil: the view from Manaus | A televisão digital no Brasil: vista de Manaus - Vicki Mayer (Liinc em Revista, 2007)
Abstract This article looks at the impacts that digital television technologies have had and likely will have in Manaus, Amazonas from the perspectives of people involved in manufacturing and development. Located both centrally in terms of global manufacturing and peripherally in terms of digital television policy, this article explores the anxieties, uncertainties, and ambivalences that the introduction of digital television has evoked with those charged with producing these technologies. Keywords: digital television, Manaus, manufacturing, production